This is the Place Salt Lake City, Utah and the Voortrekker Monument Pretoria: monuments to settler constructions of history, race, and religion. Issue 2 (3rd April 2021) - Prescott, Cynthia Culver; Rees, Nathan; Weaver-Hightower, Rebecca
ABSTRACT: This essay compares South Africa's Voortrekker Monument and the US's This is the Place monument, both built to commemorate cross-country settler movements, for how the two contemporaneous monuments memorialize the nineteenth-century historical event in the service of the racial politics of the twentieth century. While the Voortrekker monument's relief sculptures represent Black Africans as savages and intractable impediments to civilization, the This is the Place monument denies race as a factor in settlement, thus attempting to absolve settlers of the racially motivated violence that attended their colonization of the Great Basin. Perched on hilltops towering over their respective settler communities, both monuments similarly draw from the language of Beaux Arts classicism to venerate their subjects as civilizing heroes amid the chaos of Western colonialism and through comparison, we can see how both assert the colonizers' race and religion as offering a divine sanction to their acts of conquest.